2012
DOI: 10.4236/nm.2012.34049
|View full text |Cite
|
Sign up to set email alerts
|

Pinealectomy and Exogenous Melatonin Regulate Anxiety-Like and Depressive-Like Behaviors in Male and Female Wistar Rats

Abstract: <span>The main objective of this work was to </span><span>1</span><span>) study the influence of endogenous melatonin (Mel) abolishment via pi</span><span>n</span><span>ealectomy and </span><span>2</span><span>) explore exogenous Mel effect on anxiety-like and depressive-like behavior in male and female rats.</span><span> </span><span>Rats were shamoperated (Sh) or pinealectomized (Px) and following subgroups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 50 publications
2
4
1
Order By: Relevance
“…In addition, we have clearly demonstrated that the antidepressant-like activity of MEL was dose-dependent, since TIM is greatly reduced at 16 mg/kg than at 2 mg/kg dose. These results are in good agreement with data reported with our previous observations showing that chronic administration of MEL produced a real power antidepressant-like [12,13]. A similar reduction of swimming in the FST has been previously observed by Brotto et al [46].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, we have clearly demonstrated that the antidepressant-like activity of MEL was dose-dependent, since TIM is greatly reduced at 16 mg/kg than at 2 mg/kg dose. These results are in good agreement with data reported with our previous observations showing that chronic administration of MEL produced a real power antidepressant-like [12,13]. A similar reduction of swimming in the FST has been previously observed by Brotto et al [46].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we have shown that this anxiolytic-like activity of MEL depends on the used dose of the pineal hormone, its effectiveness increasing with the concentration, since its effect is greater at 16 mg/kg than at 2 mg/ kg. These results are entirely consistent with our previous observations showing that MEL caused an anxiolytic-like effect in rats [12,13]. Except study of Wong and Ong [41] in mice, showing that MEL was unable to produce any anxiolytic effectin OFT, majority, if not all other works have reported a significant reduction in anxiety behavior in animals treated with pharmacological doses of MEL, whatever the experimental conditions used or anxiogenic situations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The enhanced anxiety resulting from pineal gland removal detected a month after the surgery procedure, was confirmed in two different tests-OF and EPM. However, our previous results and literature data demonstrated a divergence with a lack of effect on anxiety, anxiolysis, or anxiogenic response resulting from pinealectomy [ 49 , 50 , 51 , 52 , 53 ]. This suggests that the difference in the strain and the testing time after pinealectomy might be an important issue determining this behavioral response.…”
Section: Discussionmentioning
confidence: 76%
“…caused behavioral anomalies such as an increase in anxiety-like and depressive-like behavior (Zahra, Siham, Abdelhalim, Aboubakr, & Ali, 2012).…”
Section: Discussionmentioning
confidence: 99%